Peta Lektur Agama Islam di Universitas Brawijaya Malang - Alfan Firmanto (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2017)
Books are a means of transmitting science and thought as well as ideology. Through diverse books of thought disseminated from the liberal, moderate to the radical. This paper intends to see the diversity and the tendency of discourse of thought contained in various Islamic books that are in public college, which at this time should get serious attention related to the issues of radicalism movement and its ideology that spread in college campus public. Brawijaya University of Malang is one of the leading state universities in East Java, which has a strategic location in the center of East Java province, so it needs serious attention related issues of ideology of radicalism. From the research map of Islamic religious director in Brawijaya University is expected to be mapped the theme of Islamic religious books in Universitas Brawijaya Malang, and can be known the themes of the most popular Islamic religious books in Universitas Brawijaya, and can be identified the tendency of thought in the theme Books of Islam in Universitas Brawijaya Malang. Keywords: Lektor Islam, Universitas Brawijaya, Buku adalah sarana transmisi ilmu pengetahuan dan pemikiran se-kali¬gus ideologi. Melalui buku beragam pemikiran disebarluaskan dari yang liberal, moderat hingga yang radikal. Tulisan ini bermaksud melihat keragaman dan kecenderungan wacana pemikiran yang terkandung dalam beragam buku Islam yang berada di perguruan tinggi umum, yang saat ini harus mendapat perhatian serius terkait adanya isu-isu gerakan radikalisme dan fahamnya yang merebak di kampus-kampus perguruan tinggi umum. Universitas Brawijaya Malang adalah salah satu universitas negeri ternama di Jawa Timur, yang memiliki lokasi strategis di tengah provinsi Jawa Timur, sehinga perlu mendapat perhatian serius terkait isu-isu ideologi radikalisme. Dari penelitian peta lektur agama Islam di Universitas Brawijaya ini diharapkan akan dapat dipetakan tema buku-buku agama Islam yang ada di Universitas Brawijaya Malang, dan dapat diketahui tema-tema buku agama Islam yang paling diminati di Universitas Brawijaya, serta dapat diidentifikasi kecenderungan pemikiran dalam tema buku-buku agama Islam di Universitas Brawijaya Malang. Kata kunci : Lektur Islam, Universitas Brawijaya,